Linear all-fiber temperature sensor based on macro-bent erbium doped fiber - Hajireza, P.; Emami, S.D.; Cham, C.L.; Kumar, D.; Harun, Sulaiman Wadi; Abdul-Rashid, H.A. (John Wiley & Sons, 2010)
A new all fiber temperature sensor is proposed and demonstrated based on a pair of 1 meter erbium-doped fiber (EDF), which are respectively macro-bent and straight. The sensor has a linear normalized loss (dB) response to temperature at 6.5 mm bending radius and 1580 nm input wavelength. The main advantage of this sensor is high temperature resolution (less than 1 degrees C) and sensitivity (0.03 dB/degrees C) due to combination of temperature dependence of EDF and bending loss. The proposed silica based sensor, has the potential for wide range and high temperature applications in harsh environments. [GRAPHICS] (C) 2010 by Astro Ltd. Published exclusively by WILEY-VCH Verlag GmbH & Co. KGaA